Uruguay : 2003 Article IV Consultation and Third Review Under the Stand-By Arrangement and Request for Modification and Waiver of Applicability of Performance Criteria-Staff Report; Staff Supplement; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uruguay. (IMF Staff Country Reports; Country Report ;, 2003)
Uruguay's performance under the Stand-By Arrangement (SBA) has been favorable, and commendable progress has been achieved in containing the crisis and stabilizing the economy. Executive Directors welcomed this development, and stressed the need to implement policies in the fiscal, banking, and structural areas. They commended the floating exchange rate regime, and the efforts of political and legal institutions in dealing with the financial crisis. They agreed that Uruguay has successfully completed the third review under the SBA, and approved waiver.